Escolha explícita e implícita de pares de estímulos - PIMENTA, Dióghenes Nobre (Universidade Federal do Pará, 2019)
This study aimed to relate research on equivalence through stimulus pairings and research on increase of attractiveness. To this end, we examined the effects of stimulus pairings (AB, BC) on the behavior of 20 subjects facing direct (BA and CA) and indirect (CB and CB) pairs, using matching-to-sample choice tests (MTS) and a liking scale. The experiment had two conditions. In the M Condition, participants were exposed to blocks of pairings and MTS; a final test was made in the form of a liking scale. The second condition (condition L) was similar to the first, except that the tests in MTS format were not carried out. Our results corroborate the data of Leader, Barnes and Smeets (1996). We also showed that over successive exposures, stimulus pairings increase response accuracy and speed. In M condition, the differential scores of liking for the direct and indirect pairs were positive, showing a strong relationship between the previous cycles and a higher score on consistent pairs. But, in L condition the results showed a significant drop in the differential scores of indirect pairs. Future studies might investigate the effects of varying the number of pairs of exposures in MTS testing.